Abnormal Large-Scale Network Activation Present in Bipolar Mania and Bipolar Depression Under Resting State - Zeng, Can; Ross, Brendan; Xue, Zhimin; Huang, Xiaojun; Wu, Guowei; Liu, Zhening; Tao, Haojuan; Pu, Weidan (Frontiers in Psychiatry, 2021)
Background: Previous studies have primarily focused on the neuropathological mechanisms of the emotional circuit present in bipolar mania and bipolar depression. Recent studies applying resting-state functional magnetic resonance imaging (fMRI) have raise the possibility of examining brain-wide networks abnormality between the two oppositional emotion states, thus this study aimed to characterize the different functional architecture represented in mania and depression by employing group independent component analysis (gICA). Method: Forty-one bipolar depressive patients, 20 bipolar manic patients, and 40 healthy controls (HCs) were recruited and received resting-state fMRI scans. gICA was applied to the brain network functional connectivity analysis. Then, we calculated the correlation between the value of between-group differences and clinical variables. Result: gICA identified fifteen components in all subjects, and ANOVA showed that functional connectivity (FC) differed significantly in the default mode network, central executive network, and frontoparietal network across the three groups. Further post-hoc t-tests showed a gradient descent of activity--depression > HC > mania--in all three networks, with the differences between depression and HCs, as well as between depression and mania, surviving after FWE correction. Moreover, central executive network and frontoparietal network activities were positively correlated with Hamilton depression scale (HAMD）scores and negatively correlated with Young manic rating scale (YMRS) scores. Conclusion: Three brain networks heighten activity in depression, but not mania; and the discrepancy regions mainly located in prefrontal, which may imply that the differences in cognition and emotion between the two states is associated with top-down regulation in task-independent networks.